Fault direction identification for wind power integration system. Issue 16 (7th January 2019) - Chen, Yu; Wen, Minghao; Hu, Liexiang; Qi, Xuanwei; Zheng, Junchao; Wang, Zhen
Abstract : Traditional directional relays of AC transmission lines are usually based on 50 Hz information in frequency domain in China. However, this conventional approach cannot provide the correct fault direction for the lines connected to wind farm because of the fault characteristics of the wind power system, that is, frequency deviation, variation of system impedance, weak feed feature, and so on. Then, the conventional approach of finding the phase angle between the fault current and a voltage signal will not identify the correct fault direction. To solve this problem, this paper proposes a novel fault direction identification method in time domain. Based on the RL model of transmission lines, opposite‐side voltages of the line can be derived with the measuring current and voltage at wind farm terminal after the fault. Then, the adjusted cosine similarity between the calculation voltage based on the RL model and the memory voltage can be acquired. If the correlation between the calculation voltage and the memory voltage is close to 1, it is a reverse fault. Otherwise, it is a forward fault. Finally, the proposed novel fault direction identification criterion is verified by the PSCAD/EMTDC‐based simulation results.